ACTION-TRAC LEGISLATIVE ACTION REPORT ISSUE: EMPLOYMENT DISCRIMINATION - HOOPER, DAVID; JACOBSON, PAUL (Tufts Archival Research Center, 2007)
Report discussing the legislative status of SB 725, a statute in Oregon allowing employers to enforce off-the-job abstinence from smoking. Outlines resources to be used in the industry action plan, including: economic analysis, legal memorandum, expert witnesses, coalition allies, grassroots mobilization, company resources and the media.